Discussion of “Information Asymmetries about Measurement Quality” - Krishnan, Ranjani (Contemporary Accounting Research, 2019)
ABSTRACT This article discusses Glover and Levine (2019). It summarizes Glover and Levine's model, its contributions, and practical implications. It also suggests empirical extensions based on the predictions of the model.